The specificity of creativity correlation with communicative and organizational abilities of student-managers - Московченко, Анжеліка Анатоліївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
The article is aimed to reveal the correlation of creativity with communicative and organizational abilities of contemporary manager’s research. The overview of theoretical and practical investigations of main manager’s professional training specifiities and necessary qualities and skills is represented. Also, the results of empirical research of manager’s creativity, prevailing thinking type, communicative and organizational abilities dynamics in the process of professional training are outlined.